STRATEGI DIGITALISASI DAN LITERASI KEUANGAN UNTUK MENINGKATKAN KEUNGGULAN KOMPETITIF SERTA KEBERLANJUTAN EKONOMI KREATIF BERBASIS KEARIFAN LOKAL DI KEPULAUAN BANGKA BELITUNG - Fatika Sari, Willa; Fauzi, Ahmad; Suaryansyah, Berandi (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This study aims to analyze the influence of digitalization and financial literacy on the sustainable competitive advantage of culinary MSMEs in Pangkalpinang City with local wisdom as a moderation variable. The method used was mixed methods with quantitative dominance through a survey of 50 culinary MSME actors, as well as interviews with the Pangkalpinang City Tourism Office and the Cooperatives, Trade, and MSMEs Office of Bangka Belitung Islands Province. Data analysis was carried out using Partial Least Squares Structural Equation Modelling (PLS-SEM). The results showed that digitalization (coefficient 0.472; p<0.05) and financial literacy (coefficient 0.351; p<0.05) had a significant positive effect on sustainable competitive advantage. Local wisdom was also shown to have a positive effect (coefficient 0.249; p<0.05) while moderating the relationship between financial literacy and sustainable competitive advantage positively (coefficient 0.301; p<0.05), but weakening the relationship between digitalization and sustainable competitive advantage (coefficient -0.205; p<0.05). These findings confirm that the integration of digitalization, financial literacy, and local wisdom is an important strategy to strengthen the competitiveness of culinary MSMEs in the archipelago, although the dominance of local culture can slow down the adoption of technology. This research makes a theoretical contribution to the integrative model of creative economy development based on local wisdom and policy recommendations to support the sustainability of MSMEs.